Exposure to topical chloramphenicol during pregnancy and the risk of congenital malformations: a Danish nationwide cohort study. (28th April 2015) - Thomseth, Vilde; Cejvanovic, Vanja; Jimenez‐Solem, Espen; Petersen, Kasper M.; Poulsen, Henrik E.; Andersen, Jon T.
Abstract Purpose To investigate whether exposure to topical chloramphenicol in the first trimester of pregnancy is associated with congenital malformations. Methods The authors conducted a nationwide cohort study including all women giving live birth between 1997 and 2011 in Denmark. All women redeeming at least one prescription of chloramphenicol eye drops or eye ointment during the first 84 days of pregnancy were identified. Logistic regression was used to estimate the odds ratios of malformations among exposed women compared to non‐exposed women. Results 966 372 births between 1997 and 2011 were included. A total of 6024 women were exposed to topical chloramphenicol in the first trimester. The rate of congenital malformations was 3.50% among offspring of exposed mothers and 3.49% among unexposed. Exposure to topical chloramphenicol in the first trimester was not associated with major congenital malformations (adjusted odds ratio = 1.06, 95% CI 0.91–1.22) or specific major malformations. The number of redeemed prescriptions decreased significantly during pregnancy as compared to before and after pregnancy (p < 0.0001). Conclusion In this study, we found no association between dispensing of chloramphenicol eye drops or eye ointment in the first trimester of pregnancy and major congenital malformations. This is in accordance with a previous study analysing the risk of systemic chloramphenicol.